Preparation method of UTSA-16 structure metal organic framework

The preparation of UTSA-16 structural metal organic frame materials through solvent-assisted ball milling method has solved the problems of high energy consumption, long time and great pollution in large-scale production in the prior art, and achieved efficient preparation of UTSA-16 materials under milder conditions effect.

CN119463206APending Publication Date: 2025-02-18FUZHOU XIERONG PRECISION IND CO LTD

Patent Information

Application Number
CN202411631517.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The prior art is used to prepare UTSA-16 structural metal organic frame materials in large-scale production, which has high energy consumption, long time and great pollution, and traditional solvent-heat and microwave synthesis methods are difficult to achieve green and environmental protection under industrial scale. synthesis.

Method used

The UTSA-16 structural metal organic frame material was prepared by solvent-assisted ball milling method. By ball milling metal salt and potassium citrate in auxiliary solvents, the pH value was adjusted, and through centrifugation, washing, drying and activation, the final 80~ The UTSA-16 structure was formed at 90°C.

Benefits of technology

The formation of UTSA-16 materials under milder conditions and in a shorter time overcomes the problems of high energy consumption, long time and high pollution in traditional methods, realizes the possibility of large-scale production, and maintains the high quality of materials Adsorption capacity and selectivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463206A_ABST
    Figure CN119463206A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a UTSA-16 structure metal organic framework, which comprises the following steps: sequentially adding a metal salt and potassium citrate into an auxiliary solvent, adding an alkaline solution, dissolving, and treating in a ball milling manner to obtain a reaction solution; centrifuging the reaction liquid, collecting a solid part, washing with diethyl ether, soaking with methanol, and drying to obtain a precursor; and activating the precursor at the temperature of 80-90 DEG C, and removing the solvent in the pore channels to obtain the metal organic framework with the UTSA-16 structure. According to the invention, the UTSA-16 is prepared by a solvent-assisted ball milling method, the problems of high energy consumption, long time and serious pollution in the previous preparation process of the UTSA-16 are solved, and the UTSA-16 can be formed under a milder condition and within a shorter time by the method; the reaction is carried out in a ball mill, the maximum synthesis amount can be enlarged along with the scale of the ball mill, the reaction takes 3 hours, heating is not needed, and the method can be put into factories for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a UTSA-16 structure metal organic framework, and belongs to the technical field of metal organic framework materials. Background Art

[0002] With the increasing development of human society and economy, problems such as over-exploitation of non-renewable energy, increasingly serious environmental pollution, and increased greenhouse gas emissions have emerged, which have attracted global attention. Therefore, while we are developing, we also need to study how to develop green. Carbon dioxide is one of the main greenhouse gases that cause climate change and global warming. Due to the continuous emissions from key industries, it has posed a major threat to human society. It is necessary to use and study new technologies and materials for capturing carbon dioxide.

[0003] The research technologies that have been developed for CO2 capture, such as chemical absorption and membrane separation, all have certain disadvantages, such as equipment corrosion, toxicity and solvent loss. In order to circumvent these defects, zeolites, activated carbons, metal-organic frameworks and covalent organic frameworks can be used. Among solid adsorbents, metal organic frameworks (MOFs) have excellent properties such as high surface area and adjustable pore size, and are a very promising adsorbent. However, to date, the development of MOFs has mainly focused on optimizing surface area, crystallinity, macromolecular encapsulation, optical properties and catalysis. The traditional solvothermal scheme for preparing UTSA-16 has been mature: take equimolar amounts of metal salts and ligand molecules, add them to a reactor with equal volumes of water and organic solvents, and heat isothermally at 120°C for a fixed time. Microwave synthesis method ( Sanjit Gaikwad, Sangil Han, A microwave method for the rapid crystallization of UTSA-16 with improved performance for CO 2 capture, Chemical Engineering Journal, 371,2019,813-820. ) is to take equimolar amounts of metal salt and ligand molecule, add them to equal volumes of water and organic solvent, then transfer the solution to a microwave glass reactor, seal it with a Teflon lid, and then put it into a microwave oven.

[0004] Although the solvothermal and microwave approaches have performed well in laboratory-scale synthesis, there is still much room for further development in large-scale environmentally friendly synthesis. The reason is that MOFs synthesis involves reactions in solvents between metal salts and organic ligands, which has production cost issues and environmental pollution risks. Therefore, it is necessary to improve materials and methods and synthesize under milder conditions so that specific MOFs materials can be synthesized on an industrial scale.

[0005] UTSA-16 is a very promising MOF material with advantages such as high adsorption capacity, high selectivity, stability in humid places and repeated use. Most of the reported syntheses of this material are based on the original UTSA-16 by Xiang et al. ( Xiang, S., He, Y., Zhang, Z. et al. Microporous metal-organic framework with potential for carbon dioxide capture at ambient conditions. Nat Commun 3, 954 (2012) ) scheme: by mixing the raw materials in a 1:1 water-ethanol mixed solvent, and then isothermally heating at 120°C for 2-3 days. The reaction process requires gradient cooling, but the maximum amount synthesized cannot exceed 1g. This solvent thermal synthesis method requires the introduction of additional capital costs to purchase special reactors for large-scale production and consumes a lot of energy. The reaction efficiency depends on the number of reactors, which needs to be increased several times before it can be used commercially. Chinese patent CN115551631A also attempts to replace a single metal with a mixed metal to synthesize UTSA-16 through a simple laboratory reflux device, but the experiment is time-consuming, the reflux preparation method used cannot be mass-produced commercially, and the ability of the synthesized product to capture CO2 is greatly reduced. Summary of the invention

[0006] In view of the defects in the prior art, the object of the present invention is to provide a method for preparing a UTSA-16 structure metal organic framework.

[0007] A method for preparing a UTSA-16 structure metal organic framework comprises the following steps: The metal salt and potassium citrate are sequentially added to the auxiliary solvent, and then an alkaline solution is added, and the pH value is adjusted to 8-13, and then the mixture is processed by ball milling to obtain a reaction solution; The reaction solution is centrifuged, the solid portion is collected, washed with ether, soaked with methanol, and dried to obtain a precursor; The precursor is activated at 80-90° C. to remove the solvent in the pores, thereby obtaining a UTSA-16 structured metal organic framework.

[0008] As a preferred embodiment, the metal salt is selected from at least one of zinc acetate, cadmium acetate, manganese acetate, cobalt acetate and manganese acetate.

[0009] As a preferred embodiment, the molar ratio of the potassium citrate to the metal salt is (0.5-5):(0.5-5); the molar ratio of the potassium citrate, the auxiliary solvent and the alkaline solution is (10-30):(1-5):(0.5-2).

[0010] As a preferred embodiment, the auxiliary solvent is at least one of water and ethanol.

[0011] As a preferred embodiment, the alkaline solution is selected from at least one of aqueous ammonia or triethylamine.

[0012] As a preferred embodiment, the rotation speed of the ball mill is 200-400 rpm.

[0013] As a preferred embodiment, the ball milling operation is carried out in a planetary ball mill, the ball milling jar is made of agate, the ball milling medium contains at least one of zirconium oxide particles, ceramic particles, and aluminum oxide particles, and the ball milling time is 1 to 6 hours.

[0014] Compared with the prior art, the present invention has the following beneficial effects: The present invention prepares UTSA-16 by a solvent-assisted ball milling method, which overcomes the problems of high energy consumption, long time and high pollution in the previous preparation process of UTSA-16. UTSA-16 can be formed under milder conditions and in a shorter time by this method; the reaction is carried out in a ball mill, and the maximum synthesis amount can be expanded with the scale of the ball mill. The reaction takes 3 hours, no heating is required, and it can be put into a factory for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings: Figure 1 The PXRD spectrum of the UTSA-16-Zn material prepared in Example 1 of the present invention; Figure 2 Comparison of the adsorption and desorption curves of CO2 at 273K between the UTSA-16-Zn material prepared in Example 1 of the present invention and the UTSA-16-Zn material prepared by the hydrothermal method in the prior art; Figure 3 This is the breakthrough curve of the UTSA-16-Zn material prepared in Example 1 of the present invention for separation of CO2 in flue gas; Figure 4 This is an operation flow chart for preparing UTSA-16-Zn material in Example 1 of the present invention; Figure 5 Comparison of the adsorption and desorption curves of CO2 of other UTSA-16 materials prepared in Examples 2 to 8 of the present invention at 273K; Figure 6 The PXRD spectrum of the material prepared in Comparative Example 1 of the present invention; Figure 7 This is the PXRD spectrum of the material prepared in Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0016] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0017] Some of the reagents used in the present invention are as follows: zinc acetate (GR, 99.5%, Warwick Raycus Co., Ltd.), potassium citrate monohydrate (AR, ≥99%, Warwick Raycus Co., Ltd.), ethanol (99.00%, Sinopharm Chemical Reagent Co., Ltd.), ether (99.00%, Sinopharm Chemical Reagent Co., Ltd.), methanol (99.00%, Sinopharm Chemical Reagent Co., Ltd.), triethylamine (99.00%, Sinopharm Chemical Reagent Co., Ltd.), and ammonia water (99.00%, Sinopharm Chemical Reagent Co., Ltd.).

[0018] All reagents were obtained from commercial sources and used without further purification. + Ultrapure water supplied by the VWR purification system.

[0019] Some of the experimental equipment used in the present invention are as follows: Planetary ball mill (QM-3SP2, Nanjing University Instrument Factory), X-ray powder diffractometer (X'perp3, Malvern Panalytical), surface adsorption instrument (ASAP2020, Mack Instruments, USA), ultrasonic instrument (KQ2000DE CNC ultrasonic cleaner, centrifugal equipment (Hunan Xiangyi TDZ4-WS desktop low-speed centrifuge).

[0020] Example 1 This embodiment provides a method for preparing a UTSA-16-Zn material, which specifically comprises the following steps: (1) 0.1 mol of zinc acetate and 0.1 mol of potassium citrate monohydrate were added to a mixed solution of 25 ml of water and ethanol (water and ethanol were prepared in a volume ratio of 1:1), and then 4 ml of triethylamine was added. After fully dissolving, the pH value of the mixed solution was adjusted to 8-13, and then the mixed solution was poured into a ball milling jar of a planetary ball mill (the ball milling jar was made of agate and contained a ball milling medium of zirconium oxide particles), and treated at a rotation speed of 300 rpm for 1-6 hours to obtain a reaction solution; (2) centrifuging the reaction solution, collecting the solid part, washing it with ether, soaking it with methanol, and drying it in an oven at 55° C. for 12 hours to obtain a precursor; (3) Activating the precursor at 85° C. to remove the solvent in the pores, thereby obtaining the UTSA-16-Zn material.

[0021] The UTSA-16-Zn material prepared in this example was characterized, and the PXRD spectrum was as follows: Figure 1 The results show that the synthesized UTSA-16-Zn and UTSA-16 are the same substance. The carbon dioxide adsorption performance of the UTSA-16-Zn material prepared in this example was compared with that of the UTSA-16-Zn prepared by the hydrothermal method. Figure 2As shown in the figure, the CO2 adsorption-desorption curves at 273K show that the adsorption capacity of UTSA-16-Zn synthesized by hydrothermal method and ball milling method is basically the same, both at 178cm 3 / cm 3 When the UTSA-16-Zn material prepared in this embodiment is used to separate CO2 from flue gas (N2 accounts for 85%, CO2 accounts for 15%), the penetration curve is as follows: Figure 3 As shown, UTSA-16-Zn can effectively separate CO2 from the mixture in the flue gas atmosphere, first eluting N2 from the outlet, while CO2 can be retained in the chromatographic column until the absorption capacity of UTSA-16-Zn is saturated, reflecting the excellent separation performance of UTSA-16-Zn for flue gas mixtures. The preparation process of UTSA-16-Zn material in this embodiment is as follows Figure 4 shown.

[0022] Example 2 This embodiment provides a method for preparing UTSA-16-Cd material, which specifically includes the following steps: Cadmium acetate (0.1 mol) and potassium citrate monohydrate (0.1 mol) were added to an agate ball mill in sequence, and 25 ml of water and 25 ml of ethanol were added in a volume ratio of 1:1. Then 4 ml of triethylamine was added to the mixed solution. After fully dissolving, the pH of the mixed solution was between 8 and 13. The ball mill was covered and placed in an oscillating ball mill (25 Hz) for ball milling. Ball milling for 1 to 5 hours, filtered, and quickly washed with ether and methanol for 3 times, respectively, and then soaked in methanol for 2 hours. Natural drying at room temperature obtained white crystals, which were directly tested by PXRD.

[0023] The prepared white crystalline MOFs material was placed under 90°C and 5umHg conditions to remove the ethanol molecules, and activated UTSA-16-Cd material was obtained after 24 hours.

[0024] Example 3 This embodiment provides a method for preparing UTSA-16-Mn material, which specifically includes the following steps: Manganese acetate (0.1 mol) and potassium citrate monohydrate (0.1 mol) were added to an agate ball mill in sequence, and 25 ml of water and 25 ml of ethanol were added in a volume ratio of 1:1. Then 4 ml of triethylamine was added to the mixed solution. After fully dissolving, the pH of the mixed solution was between 8 and 13. The ball mill was covered and placed in an oscillating ball mill (25 Hz) for ball milling. Ball milling for 1 to 5 hours, filtered, quickly washed with ether and methanol for 3 times, respectively, and then soaked in methanol for 2 hours. Natural drying at room temperature obtained white crystals, which were directly tested by PXRD.

[0025] The prepared light red crystalline MOFs material was placed under 90°C and 5umHg conditions to remove ethanol molecules, and activated UTSA-16-Mn material was obtained after 24 hours.

[0026] Example 4 This embodiment provides a method for preparing a UTSA-16-Zn / Co material, which specifically includes the following steps: Zinc acetate (0.05 mol), cobalt acetate (0.05 mol) and potassium citrate monohydrate (0.1 mol) were added to an agate ball mill in sequence, and 25 ml of water and 25 ml of ethanol were added in a volume ratio of 1:1. Then 4 ml of triethylamine was added to the mixed solution. After fully dissolving, the pH of the mixed solution was between 8 and 13. The ball mill was covered and placed in an oscillating ball mill (25 Hz) for ball milling. Ball milling for 1 to 5 hours, filtered, quickly washed with ether and methanol for 3 times, respectively, and then soaked in methanol for 2 hours, dried naturally at room temperature, and white crystals were obtained, which were directly tested by PXRD.

[0027] The prepared light red crystalline MOFs material was placed under 90°C and 5umHg conditions to remove ethanol molecules, and activated UTSA-16-Zn / Co material was obtained after 24 hours.

[0028] Example 5 This embodiment provides a method for preparing a UTSA-16-Zn / Cd material, which specifically includes the following steps: Zinc acetate (0.05 mol), cadmium acetate (0.05 mol) and potassium citrate monohydrate (0.1 mol) were added to an agate ball mill in sequence, and 25 ml of water and 25 ml of ethanol were added in a volume ratio of 1:1, and 4 ml of triethylamine was added to the mixed solution. After fully dissolving, the pH of the mixed solution was between 8-13, and the ball mill was covered and placed in an oscillating ball mill (25 Hz) for ball milling. Ball milling for 1-5 hours, filtered, quickly washed with ether and methanol for 3 times, respectively, and then soaked in methanol for 2 hours, dried naturally at room temperature, and white crystals were obtained, which were directly tested by PXRD.

[0029] The prepared white crystalline MOFs material was placed under 90°C and 5umHg to remove ethanol molecules, and activated UTSA-16-Zn / Cd material was obtained after 24 hours.

[0030] Example 6 This embodiment provides a method for preparing a UTSA-16-Zn / Mn material, which specifically includes the following steps: Zinc acetate (0.05 mol), manganese acetate (0.05 mol) and potassium citrate monohydrate (0.1 mol) were added to an agate ball mill in sequence, and 25 ml of water and 25 ml of ethanol were added in a volume ratio of 1:1, and 4 ml of triethylamine was added to the mixed solution. After fully dissolving, the pH of the mixed solution was between 8-13, and the ball mill was covered and placed in an oscillating ball mill (25 Hz) for ball milling. Ball milling for 1-5 hours, filtered, and quickly washed with ether and methanol for 3 times, respectively, and then soaked in methanol for 2 hours, and dried naturally at room temperature to obtain white crystals, which were directly tested by PXRD.

[0031] The prepared light red crystalline MOFs material was placed under 90°C and 5umHg conditions to remove ethanol molecules, and activated UTSA-16-Zn / Mn material was obtained after 24 hours.

[0032] Example 6 This embodiment provides a method for preparing a UTSA-16-Co / Cd material, which specifically includes the following steps: Cobalt acetate (0.05 mol), cadmium acetate (0.05 mol) and potassium citrate monohydrate (0.1 mol) were added to an agate ball mill in sequence, and 25 ml of water and 25 ml of ethanol were added in a volume ratio of 1:1, and 4 ml of triethylamine was added to the mixed solution. After fully dissolving, the pH of the mixed solution was between 8-13, and the ball mill was covered and placed in an oscillating ball mill (25 Hz) for ball milling. Ball milling for 1-5 hours, filtered, quickly washed with ether and methanol for 3 times, respectively, and then soaked in methanol for 2 hours, dried naturally at room temperature, and white crystals were obtained, which were directly tested by PXRD.

[0033] The prepared purple crystalline MOFs material was placed under 90°C and 5umHg conditions to remove ethanol molecules, and activated UTSA-16-Co / Cd material was obtained after 24 hours.

[0034] Example 7 This embodiment provides a method for preparing a UTSA-16-Co / Mn material, which specifically includes the following steps: Cobalt acetate (0.05 mol), manganese acetate (0.05 mol) and potassium citrate monohydrate (0.1 mol) were added to an agate ball mill in sequence, and 25 ml of water and 25 ml of ethanol were added in a volume ratio of 1:1, and 4 ml of triethylamine was added to the mixed solution. After fully dissolving, the pH of the mixed solution was between 8-13, and the ball mill was covered and placed in an oscillating ball mill (25 Hz) for ball milling. Ball milling for 1-5 hours, filtered, quickly washed with ether and methanol for 3 times, respectively, and then soaked in methanol for 2 hours, dried naturally at room temperature, and white crystals were obtained, which were directly tested by PXRD.

[0035] The prepared purple crystalline MOFs material was placed under 90°C and 5umHg to remove the ethanol molecules, and after 24 hours, the activated UTSA-16-Co / Mn material was obtained.

[0036] Example 8 This embodiment provides a method for preparing a UTSA-16-Cd / Mn material, which specifically includes the following steps: Cadmium acetate (0.05 mol), manganese acetate (0.05 mol) and potassium citrate monohydrate (0.1 mol) were added to an agate ball mill in sequence, and 25 ml of water and 25 ml of ethanol were added in a volume ratio of 1:1, and 4 ml of triethylamine was added to the mixed solution. After fully dissolving, the pH of the mixed solution was between 8 and 13. The ball mill was covered and placed in an oscillating ball mill (25 Hz) for ball milling. Ball milling for 1 to 5 hours, filtered, quickly washed with ether and methanol for 3 times, respectively, and then soaked in methanol for 2 hours, dried naturally at room temperature, and white crystals were obtained, which were directly tested by PXRD.

[0037] The UTSA-16-M material obtained in Examples 2 to 8 was tested for CO2 adsorption and desorption performance at 273K. The results are as follows: Figure 5 As shown, the adsorption capacity of UTSA-16-M is between 166 and 152 cm 3 / cm 3 For single metal UTSA-16-M materials, the adsorption amounts decrease from Zn, Mn, and Cd in sequence; for mixed metal UTSA-16-M materials, the adsorption amounts decrease from Zn / Co, Co / Mn, Zn / Mn, Cd / Mn, and Zn / Cd in sequence.

[0038] Comparative Example 1 The difference between this comparative example and Example 1 is that no alkaline solution is added during the preparation process. The PXRD pattern of the product is as follows: Figure 6 As shown, the UTSA-16-Zn prepared by ball milling without adding alkaline solution has an additional peak at 12° compared with the simulated peak, and the main peak has a certain degree of left shift, indicating that the crystal framework has changed. The possible reason is that the large amount of acetate molecules added will affect the acidity and alkalinity of the solution, causing the synthesized UTSA-16-Zn crystal structure to be corroded by the acidic solvent, which in turn leads to changes in the PXRD spectrum.

[0039] Comparative Example 2 The difference between this comparative example and Example 1 is that the ratio of water to ethanol added to the mixed solution during the preparation process is 2:1. The PXRD spectrum of the product is as follows: Figure 7As shown in the figure, it shows that when the ratio of water to ethanol is changed, the spectrum peaks of the prepared UTSA-16-Zn are more different from the simulated peaks, indicating that the target crystal framework structure has not been synthesized. The possible reason is that if the proportion of water in the solvent is too high, the crystal nucleation rate is slow, the target crystal cannot be precipitated, or the precipitated crystal quality is poor. The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.

Claims

1. A method for preparing a UTSA-16 structure metal organic framework, characterized in that: The steps include: The metal salt and potassium citrate are sequentially added to the auxiliary solvent, and then an alkaline solution is added, and the pH value is adjusted to 8-13, and then the mixture is processed by ball milling to obtain a reaction solution; The reaction solution is centrifuged, the solid portion is collected, washed with ether, soaked with methanol, and dried to obtain a precursor; The precursor is activated at 80-90° C. to remove the solvent in the pores, thereby obtaining a UTSA-16 structured metal organic framework.

2. The method for preparing the UTSA-16 structure metal organic framework according to claim 1, characterized in that: The metal salt is selected from at least one of zinc acetate, cadmium acetate, manganese acetate, cobalt acetate and manganese acetate.

3. The method for preparing the UTSA-16 structure metal organic framework according to claim 1, characterized in that: The molar ratio of the potassium citrate to the metal salt is (0.5-5):(0.5-5); the molar ratio of the potassium citrate, the auxiliary solvent and the alkaline solution is (10-30):(1-5):(0.5-2).

4. The method for preparing the UTSA-16 structure metal organic framework according to claim 1 or 3, characterized in that: The auxiliary solvent is at least one of water and ethanol.

5. The method for preparing the UTSA-16 structure metal organic framework according to claim 1 or 3, characterized in that: The alkaline solution is selected from at least one of aqueous ammonia and triethylamine.

6. The method for preparing the UTSA-16 structure metal organic framework according to claim 1, characterized in that: The rotation speed of the ball mill is 200-400 rpm.

7. The method for preparing the UTSA-16 structure metal organic framework according to claim 1, characterized in that: The ball milling operation is carried out in a planetary ball mill, the ball milling jar is made of agate, the ball milling medium contains at least one of zirconium oxide particles, ceramic particles, and aluminum oxide particles, and the ball milling time is 1 to 6 hours.

Citation Information

Patent Citations

  • Mixed metal strategy for rapidly synthesizing metal-organic framework under environmental condition

    CN115551631A

Cited By

  • Flaky bismuth-based metal organic framework material and preparation method thereof

    CN120504842A

  • A sheet-like bismuth-based metal organic framework material and a preparation method thereof

    CN120504842B

  • Method for preparing UTSA-16 material through two-step ball milling and product

    CN121226757A

  • Method for preparing UTSA-16 material through ball milling and product

    CN121226758A